Helioseismology space and ground-based studies - Kostik, R.I.; Osipov, S.N.; Khomenko, E.V.; Lebedev, N.I. (Кинематика и физика небесных тел, 2005)
We give a preliminary report on the observations of solar irradiance fluctuations with the DIFOS photometer aboard the Russian–Ukrainian satellite CORONAS-F launched in 2001. In addition, the parallel ground-based spectral observations (VTT, Tenerife) carried out with 20-day observing space campaign are described.